2018
DOI: 10.1161/circinterventions.118.006837
|View full text |Cite
|
Sign up to set email alerts
|

Performance of PRECISE-DAPT Score for Predicting Bleeding Complication During Dual Antiplatelet Therapy

Abstract: Background: Dual antiplatelet therapy (DAPT) helps prevent ischemic events after coronary stenting but comes with an increased risk of bleeding. Several risk scores have been proposed for the management of patients receiving DAPT, but no standardized tool exists for the purpose. We sought to compare the performance of the new PRECISE-DAPT (Predicting Bleeding Complication in Patients Undergoing Stent Implantation and Subsequent Dual Antiplatelet Therapy), CRUSADE (Can Rapid Risk Stratification of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…The 2017 European Society of Cardiology Focused Update on DAPT recommended the PRECISE-DAPT score for guidance over the duration of DAPT [22]. In the previous study, we validated the performance of this score for predicting bleeding events in Korean patients undergoing PCI [23]. The simplified PRECISE-DAPT score without WBC count has a similar predictive value for bleeding after PCI [24].…”
Section: Discussionmentioning
confidence: 83%
“…The 2017 European Society of Cardiology Focused Update on DAPT recommended the PRECISE-DAPT score for guidance over the duration of DAPT [22]. In the previous study, we validated the performance of this score for predicting bleeding events in Korean patients undergoing PCI [23]. The simplified PRECISE-DAPT score without WBC count has a similar predictive value for bleeding after PCI [24].…”
Section: Discussionmentioning
confidence: 83%
“…It should also be mentioned that high as many as 20% of our patients had undergone a PCI with total stent length > 60 mm (of note, the proportion of patients with long stent stenting in Bern PCI registry was 6.5%). Third, there is evidence demonstrating an increased risk of bleeding events in patients with baseline higher categories of bleeding risk prediction scores [32,33]. Lower bleeding risk of our study patients, compared with Bern PCI registry (PRECISE-DAPT score: 10.6 ± 8.5 vs. 20.6 ± 13.3), may have partly explain difference in the risk of clinically relevant bleeding.…”
Section: Discussionmentioning
confidence: 65%
“…Bleeding events related to potent P2Y12 inhibitors [ 7 , 8 ], or triple therapy (DAPT plus oral anticoagulant) [ 25 ], or high bleeding risk (HBR) [ 26 , 27 ], have resulted in adverse outcomes. Previously we reported that the PRECISE-DAPT Score was validated to predict bleeding events in Korean patients taking DAPT after PCI [ 11 ]. Additionally, these bleeding events occurred more frequently in the first month after PCI resulting in a hazard ratio of 4.0 (bleedings vs. MACE) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…After acute or subacute stages of PCI in ACS patients, bleeding events are more problematic during the maintenance dose periods [ 11 ]. The recent TICO and TWILIGHT studies demonstrated that de-escalation by dropping aspirin at 3 months resulted in favorable outcomes [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%